Do 25 years old skid tracks restrict growth and survival? - Boström, Malin (2015)
The rainforests of the world are important not only to the countries in which they grow but to the world as a whole. They influence oxygen and water circulation as well as carbon sequestration which in turn affect global radiation and global warming. The forest also have great value and in Malaysia as in many other tropical countries large volumes are harvested which leaves great areas of degraded forest with little growth and biological diversity. Due to their low financial value these forests are often transformed and used for other purposes than forestry such as oil palm plantations. The trees are often transported out of the forest using large bulldozers. They are heavy which causes compaction of the forest floor and during transport the top soil layers are moved to improve mobility. In the years that follows runoff in the skid tracks can be high and leaking of nutrients and other material is often higher in the skid tracks compared to outside. This causes negative effects on the regeneration in terms of growth, survival and diversity. The effects can remain for many years after logging. In Sabah on Malaysian Borneo a project to rehabilitate forest and restore forest values is running. The project combines replanting trees of high ecosystem values with research. The targeted area has been affected by both logging and forest fires in the eighties but has since then been left until the rehabilitation operation in 1998. One of the methods used is planting in two meters wide cleared lines. This study has been made within this project and focus on the mortality and growth on skid tracks. Is there a detectable difference? Is the ground still more compacted on the skid tracks? Is there any difference in the conditions that might affect growth and mortality such as levels of organic carbon, nitrogen phosphorus and clay? The location of this study is in an east facing slope that in parts connect to a creak at the bottom. This area was planted in 2008. For all the planted trees in the area light conditions, height, diameter at breast height (Dbh), species and mortality has been recorded as well as whether or not the plant is located on skid track. Ten species has been selected for a more thorough investigation.For each of these species 16 specimens have been choosen and in the soil surrounding these penetration resistance has been measured and soil samples has been taken to measure bulk density and levels of phosphorus, nitrogen and organic carbon. The results showed no detectable difference in mortality but the trees were both higher and had a larger Dbh on the skid tracks. Light was also higher on skid tracks which could be part of the reason of the higher growth as light showed to increase both Dbh and height. Of the other tested variables only penetration resistance showed correlation with skid tracks. The resistance was higher on the tracks which might be explained by the uneven distribution of skid tracks with more tracks located at the bottom of the slope where there is more sand in the ground. There was no detectable correlation between any of the tested variables and mortality. Apart from light higher bulk density and lower amounts of organic carbon and available phosphorus was correlated with higher growth. However all the tested soil properties, apart from penetration resistance, showed to be correlated and it is possible that growth is strongly affected with something else that is in turn connected to the measured variables.